IMF Staff papers : Volume 5 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1956)
The purpose of this paper is to describe the role and the operating significance of IMF quotas. Each member of the IMF has a quota, the functions of which are threefold. These functions are interrelated, but the attempt to find a series of figures that would effectively perform all these functions for each member necessitated a large amount of compromise in the determination of quotas. A quota determines the subscription or contribution of each member to the capital of the IMF; and the total of the quotas of all members determines the size of the IMF's financial resources. Each member is required to pay to the IMF of its quota in gold, and the balance in its own currency. Apart from any retained profits or accumulated losses, quotas directly determine the total assets of the IMF. Assets can be increased only by admitting new members or by increasing the quotas of existing members, though the Fund may under prescribed conditions increase the funds at its disposal by borrowing.